2019
DOI: 10.1063/1.5079872
|View full text |Cite
|
Sign up to set email alerts
|

Mirrored enhanced Howland current source with feedback control

Abstract: An impedance spectrum is calculated by the ratio between an injecting current and a resulting measured voltage, which allows the extraction of electrical properties from the material under study. The current source is considered an essential block to deliver a controlled current to a wide range of working loads and large bandwidth. To comply with such requirements, the current source output impedance must be much higher than the load impedance at each discrete frequency within the range. However, stray capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A full circuit schematic is shown in the supplement. We utilized a mirrored Howland current source as proposed by 29,30 for each stimulator channel. We additionally included a DC blocking capacitor at the output, to prevent DC leakage during stimulation, which can skew recruitment curves 31 .…”
Section: Methodsmentioning
confidence: 99%
“…A full circuit schematic is shown in the supplement. We utilized a mirrored Howland current source as proposed by 29,30 for each stimulator channel. We additionally included a DC blocking capacitor at the output, to prevent DC leakage during stimulation, which can skew recruitment curves 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Wilson et al, 2001). A recent development of the former approach has shown that using the measured current to control the output current from the current source gives a current source with a high output impedance when multiplexers are used (Sirtoli et al, 2019). All these approaches have substantial cost and complexity implications but should be considered as part of future developments.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the literature and technical documentation showed the existence of two basic types of circuit configurations that work with floating or grounded load. In previous works, 5–14 different circuits of voltage‐to‐current converters with grounded load are presented, in which various useful structural modifications and frequency compensations with external passive components are proposed for improving the stability in a given frequency range, as well as increasing the value of the output resistance. Moreover, the majority of the electronic circuits 3–6,8–12,14 are based on the Improved Howland Current Pump, which uses one op‐amp and five (or six) resistors.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, 5–14 different circuits of voltage‐to‐current converters with grounded load are presented, in which various useful structural modifications and frequency compensations with external passive components are proposed for improving the stability in a given frequency range, as well as increasing the value of the output resistance. Moreover, the majority of the electronic circuits 3–6,8–12,14 are based on the Improved Howland Current Pump, which uses one op‐amp and five (or six) resistors. For the Improved Howland Current Pump, with an accurate selection of the ratios of the resistors and proper selection of the op‐amp, the independence of the output current from the voltage drop over the load can be achieved, as well as the bandwidth can up to about 100 kHz 6,10,12–14 and in some cases up to 1 MHz 5,8,9,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation